ANALISIS TINGKAT PENCAPAIAN PENDIDIKAN WAJIB BELAJAR 9 TAHUN ANTAR PROVINSI DI INDONESIA - Wardhana, Adhitya; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023, 2023)
This study aims to analyze the extent to which the independent variables, namely education sector government spending (PPEND), student and teacher ratio (RMG), GRDP per capita (PDRBKAP), health sector government spending (PKES), and some schools (INFRA) can influence the dependent variables, namely, the 9-year compulsory education program is shown by completing elementary and junior high school education. The scope of the research is regional scale using data combined from cross sections and time series (panel data). The research period starts from 2016- 2020. The model used is two equations by separating the independent variables of elementary and junior high school graduates. The estimation results using panel data regression analysis show that only the GRDP per capita variable (PDRBKAP) does not significantly influence the elementary school and junior high school variables, while the other independent variables are government expenditure in the education sector (PPEND), student and teacher ratio (RMG ), government spending in the health sector (PKES) and the number of schools (INFRA) have a significant effect on the dependent variable in each equation.